23rd IEEE Real-Time Systems Symposium, 2002. RTSS 2002.
DOI: 10.1109/real.2002.1181569
|View full text |Cite
|
Sign up to set email alerts
|

Soft real-time scheduling on simultaneous multithreaded processors

Abstract: Simultaneous multithreading (SMT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 17 publications
0
64
1
Order By: Relevance
“…He did not specify the execution order, but he used an out-of-order processor as base architecture and so did most of the later SMT researchers. Consequently, most of the work on real-time and SMT is also based on out-of-order pipelines [3][4][5][6]. But the unpredictability of out-of-order pipelines does not allow hard real-time execution, only soft real-time scheduling is addressed.…”
Section: Related Workmentioning
confidence: 99%
“…He did not specify the execution order, but he used an out-of-order processor as base architecture and so did most of the later SMT researchers. Consequently, most of the work on real-time and SMT is also based on out-of-order pipelines [3][4][5][6]. But the unpredictability of out-of-order pipelines does not allow hard real-time execution, only soft real-time scheduling is addressed.…”
Section: Related Workmentioning
confidence: 99%
“…Peha et al [2] suggested some new approaches towards scheduling but they are not QoS-aware. Matschulat et al [3] and Tomoyoshi et al [4] have studied QoS [5][6][7] in embedded systems but none of them considered Markov chains. The concept of system QoS based on Markov statistics, is for the first time we have worked out here to our best knowledge.…”
Section: Related Workmentioning
confidence: 99%
“…Real-time scheduling by software on an SMT processor is detailed in [8]. This research focuses on soft real-time scheduling for simultaneous execution threads and their shared resources on the SMT processor.…”
Section: Related Workmentioning
confidence: 99%
“…The RMT architecture accurately guarantees the execution time of the prioritized threads. Software scheduling such as in [8] may improve execution time precision of lower priority threads.…”
Section: Pipelinementioning
confidence: 99%